Environmental Justice and Green Infrastructure in the Ruhr. From Distributive to Institutional Conceptions of Justice - Zimmermann, Karsten; Lee, Dahae (Frontiers in Sustainable Cities, 2021)
Over the last 50 years, the Ruhr region experienced a remarkable transformation from an industrial to a post-industrial region. With regard to the rehabilitation of the environmental damages of more than 100 years of coal mining and steel production, investment in green infrastructure, and the creation of regional landscape parks constituted one of the main pillars of the economic and physical transformation of the region. However, little is known about the social effects of this green transformation. Many observers state that the Ruhr area is sharply divided by an east–west line (the A40 Highway) and in fact the Emscher zone was hit most by environmental degradation. We argue that environmental justice is a question of scale. While on the regional scale, the investments made in the Emscher zone can be seen as a trial to balance and repair a long-standing unequal provision with environmental qualities (not least parks), on a smaller scale (i.e., cities and neighbourhoods) we can demonstrate that in the cities of the Emscher zone environmental inequality is still observable. Some neighbourhoods benefit stronger from investment in regional parks and green infrastructure than others. The paper will describe the Emscher green regeneration programme and will give detailed insights into two cities of the Ruhr (including maps and data analysis).